Penerapan Algoritma Vertical Bit Rotation Dalam Pengamanan Data Sekolah - Aulia, Rachmat; Dafitri, Haida; Irwandi, Bayu; Liza, Rizko (Forum Kerjasama Pendidikan Tinggi, 2022)
Cryptography is a science based on mathematical techniques related to security and information such as confidentiality, data integrity and entity authentication. In other words, it means to conduct the process of encoding libraries that act as ciphers, and converting the original text into illegal it. The implementation of encryption process requires a public and a secret key. One of the cryptography techniques applied in the research is the Algorithm of Vertical Bit Rotation (VBR). The VBR is a technique that implements an asymmetric key, which it has a same value in term of data encryption and decryption. The technique is also applied in the shape of an application designed in this research, then have ability to run encryption and decryption process in the format of text file, that providing data security to avoid eavesdropping and illegal access from irresponsible parties. The result done by using VBR is it may run well so have ability to restore the condition of the data in plaintext, then in addition information, encrypted data cannot be returned to its pure form without using a valid key